Capim Massai manejado em sistemas de produção com doses de nitrogênio e potássio - Silva, Francianne Costa (Universidade Federal do Tocantins, 2017)
Objective was to assess morphological, structural and agronomic aspects of Massai grass under fertilization with formulated 20: 0: 20. The test was conducted at the Federal University of Tocantins, School of Veterinary Medicine and Animal Science August 2014 to June 2015. Were evaluated doses 0; 25; 50; 75 kg / ha of N and K2O always performed after the grass defoliation Massai, which were arranged in a completely randomized design with four replications of 9 m2 (3x3), totalizing 16 experimental units. The Masai grass off the defoliation was performed at the level of 10 cm above ground level, where after the time of three sheets recovery per tiller fully cut. To morphogenetic response was significant for fertilization levels where the (TapF) ranged from 4.95 when not fertilized to 10.98 when using the dose and 75 kg NK2O / ha. Observed reduction phyllochron, from 23 to 8 days compared to zero doses and 75 kg of NK2O. The elongation rate of leaf blade, stem and leaf senescence were increased due to the increase of the doses of fertilizer in 33,29 and 23% coming from 11.086 to 32.8135, 0.3311 to 1.1411 and 0.0499 to 7.0485 mm / perf / day, respectively, for the doses 0 and 75. The NFV has not changed depending on the dose of fertilizer and reached average values of 3.81 leaves / tillers. Fertilization reduced the DVF 71 and 40 days / leaves to the lower and higher dose of fertilizer, respectively.The DVF said linear and negatively to nitrogen fertilization. The population density of tillers showed a linear effect with the increase in nitrogen, with estimated 1807 and 2339 tillers / m2 in doses 0 and 75 kg / ha of NK2O respectively. In response morphogenetic and structural variations TPBF was increased with increasing fertilization, reaching maximum values of 236.49 kgMS / ha / day at the dose of 50 kg / ha / NK2O cycle, 56% higher than the dose 0. The accumulation rate of (TACF), close to 50 kg / NK2O, where he obtained a production of 173.94 kg / ha / day higher than 42% the dose 0. Thatched production 43.43 kg / ha / day, 78 % higher than unfertilized. Its maximum leaf blade production rate occurred at a dose of 50 kg / NK2O with production of 194.39 kg / ha / day 51% higher dose 0. Leaf blade accumulation rate achieved its maximum with 49.37 kg / NK2O and an output of 131.74 kg / ha / day being 40% higher when unfertilized. Based on NK2O fertilization results performed with the formulated 20: 0: 20 concludes improvement in morphogenetic and structural characteristics, resulting increases in Massai grass growth. However, more studies should be conducted, especially evaluating the best time to perform the defoliation.